Cholestatic liver injury due to leukemic infiltration in HOX11-positive acute monocytic leukemia: a case report - Xu, Huiping; She, Qunqing; Xie, Linjun (Frontiers in Oncology, 2025)
We report the case of a 78-year-old male who was diagnosed with HOX11-positive acute monocytic leukemia (AML-M5), complicated by leukemic hepatic infiltration and cholestatic liver injury. Initial management included hydroxyurea and liver-protective therapies; however, liver dysfunction progressed despite treatment. With the patient’s liver function deteriorating, chemotherapy with venetoclax and azacitidine was initiated under close monitoring, along with intensive supportive care including methylprednisolone. This regimen choice was based on a careful assessment of the hepatotoxicity profiles of these drugs in conjunction with the patient’s hepatic function. As the leukemic burden decreased, liver function gradually improved, and the patient achieved hematologic recovery sufficient for discharge. This case highlights the challenges of treating elderly AML-M5 patients with hepatic infiltration and emphasizes the importance of early recognition and individualized treatment strategies and the potential benefits of dose-adjusted induction therapy tailored according to the hepatotoxicity profiles of the drugs and the patient’s hepatic function.